Personalized Web-based Recipe Repository - Shahimi, Shamil; Abu Bakar, Nur Azzah; ChePa, Noraziah (Multidisciplinary Applied Research and Innovation, 2023)
A large number of dedicated websites about cooking have popped up on the Internet during the past few years, allowing people to access thousands of recipes from all over the world. Choosing the best website is challenging due to the abundance of the so-called cooking blogs. In response to the challenge, a Personalized Web-Based Recipe Repository system thas been developed to manage recipes in an innovative way. Users not only can store and find new recipes, but can also save their personal recipes, as well as the ability to modify or remove their own recipes at any time. JavaScript, PHP, CSS and MySQL were used in the construction of the website and followed the standard development methodology which consists of phases such as planning, requirement gathering, design, development and evaluation which take nine months to complete. The usability test was carried out with 30 respondents. The results revealed the score above 90 percent for all the tested items which include design and layout, simplicity, effectiveness, learnability and satisfaction. The website has several advantages, such as making it easier and more flexible for users to look for different recipes, which saves them time from having to go through numerous food blogs. Additionally, it can also serve as a repository for the user’s own recipes and suggest similar ones that they might like. At the same time, it gives the user the desired flexibility and a more engaging and exciting manner of searching, saving, modifying, and removing recipes, eliciting a multi-sensory experience for the user. The inclusion of a recommendation function provides an entertaining approach for users to look for recipes.